Designing a Data Mart at the Indonesian Psychological Healthcare Center Using Pentaho - Octarifa Angela; Jap Tji Beng; Dedi Trisnawarman; Sri Tiatri; Toong Hai Sam; Rhalf Jayson F. Guanco; Rahmiyana Nurkholiza; Vienchenzia Oeyta Dwitama Dinatha (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Critical data is essential for organisational success, providing essential information for decision-making. This study focuses on the Indonesian Mental Health Centre (IndoPsyCare), which utilises data to improve service performance. The research aims to design a data mart to support analytical needs by transforming the Online Transaction Processing (OLTP) database into Online Analytical Processing (OLAP). This design follows Kimball's Nine-Step Approach and integrates the Extract, Transform, Load (ETL) process. Data was collected from August 2023 to August 2024 through interviews and electronic documentation. The system was implemented using Microsoft SQL Server Management Studio 18 and Pentaho Data Integration. The resulting data mart uses a star schema with fact and dimension tables tailored to stakeholder needs, particularly in appointment analysis. Findings indicate that the data mart facilitates efficient access, targeted analysis, and improved query performance, thereby supporting IndoPsyCare's decision-making and overall service optimisation.